Engineering MoOx/MXene Hole Transfer Layers for Unexpected Boosting of Photoelectrochemical Water Oxidation. (21st February 2022) - Song, Yurou; Zhang, Xiaomeng; Zhang, Yanxue; Zhai, Panlong; Li, Zhuwei; Jin, Dingfeng; Cao, Jiaqi; Wang, Chen; Zhang, Bo; Gao, Junfeng; Sun, Licheng; Hou, Jungang
Abstract: The development of semiconductor photoanodes is of great practical interest for the realization of photoelectrochemical (PEC) water splitting. Herein, MXene quantum dots (MQD) were grafted on a BiVO4 substrate, then a MoO x layer by combining an ultrathin oxyhydroxide oxygen evolution cocatalyst (OEC) was constructed as an integrated photoanode. The OEC/MoO x /MQD/BiVO4 array not only achieves a current density of 5.85 mA cm −2 at 1.23 V versus a reversible hydrogen electrode (vs. RHE), but also enhances photostability. From electrochemical analysis and density functional theory calculations, high PEC performance is ascribed to the incorporation of MoO x /MQD as hole transfer layers, retarding charge recombination, promoting hole transfer and accelerating water splitting kinetics. This proof‐of‐principle work not only demonstrates the potential utilization of hole transfer layers, but also sheds light on rational design and fabrication of integrated photoanodes for feasible solar energy conversion. Abstract : MXene quantum dots were grafted on a BiVO4 substrate, then a MoO x layer combining an ultrathin oxyhydroxide oxygen evolution cocatalyst was constructed as a promising model system of an integrated photoanode. The OEC/MoO x /MQD/BiVO4 array not only achieves a current density of 5.85 mA cm −2 at 1.23 V vs. RHE, but also remarkably enhances photostability.